The anatomy of an albite-type granitic pegmatite from the Totoral pegmatite field, San Luis, Argentina - Galliski, Miguel Angel (2015)
The Independencia Argentina albite-type granitic pegmatite is the most distal differentiate in the Cerro La Torre pegmatite group, located in the Eastern Pampean Ranges of Argentina. It is a zoned pegmatite formed at two main stages that probably shared the same origin but had separate evolutions. The product of the first stage was a pegmatite dominated by albite, quartz and muscovite, with rare K-feldspar and muscovite + albite pseudomorphs after spodumene, and accessory columbite-group minerals, beryl, fuorapatite as well as garnet. This first-stage pegmatite was emplaced forcefully and crystallized syn-kinematically. Resulting boudinage and necking-down produced the main body, bulbous in shape and asymmetric in zoning. This pegmatite was subsequently intruded by a melt that solidified to a very fine-grained, saccharoidal albite unit, composed in excess of 97 % by Ab99.1-99.6, with accessory columbite-group minerals and fluorapatite. The normative mineral composition of this unit corresponds very well with that of the experimental products of protracted fractionation of rare-element pegmatite melts, with high Na/K ratios and HFSE enrichment. The spatial and temporal association of the two pegmatitic melts, one enriched in H2O and the other one more evolved, Narich, almost alkaline and flux-bearing, strongly suggests that the two are cogenetic. They probably represent products of a rare-element pegmatite magma differentiation at depth that were extracted at different stages of its crystallization and emplaced at higher crustal levels.